2003
DOI: 10.1007/s00299-003-0695-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening of mulberry ( Morus spp.) for salinity tolerance

Abstract: An efficient in vitro screening method has been developed for mulberry ( Morus spp. ) to screen salinity-tolerant genotypes from a large population. Axillary buds from field-grown plants were cultured on MS medium containing five different concentrations (0.0%, 0.25%, 0.5%, 0.75% and 1.00%) of sodium chloride (NaCl) in order to study the shoot growth pattern. Rooting was also tested at four different concentrations of NaCl (0.0%, 0.1%, 0.2% and 0.3.%). NaCl has been found to inhibit the growth and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 11 publications
9
58
0
Order By: Relevance
“…Other investigators have reported the use of NaCl for in vitro salinity screening in other species of plants (Vijayan et al 2003;Zhao et al 2009), but the concentrations used have not been as high as those used in this study. All growth and physiological parameters were significantly affected by salt stress.…”
Section: Discussionmentioning
confidence: 88%
“…Other investigators have reported the use of NaCl for in vitro salinity screening in other species of plants (Vijayan et al 2003;Zhao et al 2009), but the concentrations used have not been as high as those used in this study. All growth and physiological parameters were significantly affected by salt stress.…”
Section: Discussionmentioning
confidence: 88%
“…The addition of NaCl to the culture media decreased the osmotic potential of the media inducing salinity stress that adversely affected the callus growth. Several authors reported the use of NaCl for in vitro salinity screening in different plants (Vijayan et al, 2003). In this study, the adaption capacity to different salt level varies with the genotype's degree of tolerance.…”
Section: Biomass Changing Of Callus On Treatmentmentioning
confidence: 84%
“…In vitro techniques make it possible to screen the required number of genotypes rapidly since in vitro plant exhibit their capacity to withstand the stress (Tewary et al, 2000). In many species like tobacco, grape, rice citrus and carrot salt tolerant lines have been isolated using in vitro techniques (Vijayan et al, 2003;Tewary et al, 2000;Ben-Hayyim, 1987). Tomato is sensitive to moderate levels of salt in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its leaving the border lines, data was recorded in 5 crop the available information on important morphological, biochemical, anatomical, reproductive and physiological characteristics of the 162 mulberry accessions present in the germplasm bank of Central Sericultural Research and Training Institute, Berhampore, West Bengal [15][16][17][18][19], 23 potential parents were selected and systematic breeding was effected as described by reference [20]. From the seedling of 3500 seed, 2700 hybrids were transferred to progeny row trial and evaluated for two years for leaf yield and growth parameters (data not shown).…”
Section: Methodsmentioning
confidence: 99%